Developing a monitoring and evaluation framework for the mentoring component of the Principals Academy Trust - Kölzer, Joshua (School of Management Studies, 2023)
The Principals Academy Trust (PAT) is a non-profit organisation, whose programme is focused on improving the leadership competencies of school principals in poor and marginalised communities in South Africa largely through mentoring. While PAT collects quantitative data to monitor the performance of the schools in their programme, currently no data is collected to measure the extent to which PAT's mentoring efforts are positively impacting the schools' culture or climate. This study sought to develop an M&E framework for the mentoring component of the PAT programme. The M&E framework is informed by an extensive programme theory evaluation. The framework is designed to enable PAT to monitor and evaluate the potential changes in school climate and culture as a result of the mentoring component of the PAT programme. For the purposes of this study, Donaldson's step-by-step model for conducting a programme theory evaluation was merged with Markiewicz & Patrick's step-by-step guide on how to develop an M&E framework. The aim of this approach was to ensure that the results of the theory evaluation provide the foundation for the M&E framework. A combination of desk research, focus groups with PAT's programme staff and a number of semi-structured interviews with the head mentor and the fundraising consultant for PAT, was used to create the M&E framework. The results of the theory evaluation indicate that according to recent social science research in the field of education, the causality assumed in PAT's programme theory is plausible. The theory evaluation concludes that it is plausible to assume positive impacts on school culture and climate through systematic mentoring of school principals. The results of the development of the M&E framework are presented as a complete monitoring plan, evaluation plan, data collection and management plan, data analysis and synthesis strategy, learning strategy and implementation plan.